Can someone explain how this:

Operating Margin= pQ - (F + vQ) / pQ

Got to this, solving for Q:

Q = F / p (1 - v/p - (operating margin))

Any help with the step by step solution would be very much appreciated!

Can someone explain how this:

Operating Margin= pQ - (F + vQ) / pQ

Got to this, solving for Q:

Q = F / p (1 - v/p - (operating margin))

Any help with the step by step solution would be very much appreciated!

Operating Margin= pQ - (F + vQ) / pQ

Got to this, solving for Q:

Q = F / p (1 - v/p - (operating margin))

Any help with the step by step solution would be very much appreciated!

I cant read it with the words so I'm doing like this:Can someone explain how this:

Operating Margin= pQ - (F + vQ) / pQ

Got to this, solving for Q:

Q = F / p (1 - v/p - (operating margin))

But if you plug in p = 1, Q = 2, F = 3, v = 4 (these are just numbers I picked out of the air), you get two different numbers for M so the 2nd eqn can't be just a rearrangement of the 1st. You cant get from 1st to 2nd.